PROGRAM KOTA SEHAT DALAM PERSPEKTIF COLLABORATIVE GOVERNANCE (Studi pada Pemerintah Kota Batu) - Mindarti, Lely Indah; Masyhuri, Aziz; Ulum, Mochamad Chazienul (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
This study aims to determine, describe and analyze the Healthy Cities Program in the perspective of collaborative governance in Batu City. This type of research is a descriptive study with a qualitative approach. The theory used is governance, collaborative governance, sustainable development and Healthy City. Data analysis techniques using the Spradley model which includes domain analysis, taxonomic analysis, componventional analysis, and cultural theme analysis. The results showed that the Healthy Cities Program implemented by the Batu City Government had been running well, seen from the collaborative governance model indicators put forward by Ansell and Gash covering the collaborative process consisting of meeting face to face, building trust, the process of achieving commitment, understanding for joint decisions and interim results. Furthermore, the initial conditions consist of resource imbalances, incentives to participate, and background history. Next the institutional design consists of stakeholders involved, ground rules, and transparency. Then facilitative leadership includes broad influence and control, facilitation of productive groups, and expanding relationships or networks. Collaboration between stakeholders during the implementation of the Healthy Cities Program starts from the planning stage, the implementation of activities to the evaluation of the program. Stakeholders involved in the Healthy Cities Program from the government include the Health Service, the Environmental Service, the Tourism Service, the Food Security Service, and the Bappelitbangda. Next stakeholders include the community (FKBS, forkom, and working group) while the private sector is represented by the manager of the Selecta tourism object and the Batu Flower Garden (BFG). The Healthy Cities Program implemented by the Batu City Government consists of four arrangements, namely, an independent healthy community order, a healthy tourism order, a food and nutrition security order, and a healthy infrastructure and infrastructure settlement arrangement. Batu City Government continues to develop the Healthy Cities Program to improve the health, comfort and welfare of the community.